Laboratory Evaluations of the Fractions Efficacy of Annona senegalensis (Annonaceae) Leaf Extract on Immature Stage Development of Malarial and Filarial Mosquito Vectors - Younoussa Lame; EliasNchiwan Nukenine; Danga Yinyang-; Ajaegbu Eze-Elijah; Charles Okechukwu-Esimone (Tehran University of Medical Sciences, 2015)
Background: Within the framework to control mosquitoes, ovicidal, larvicidal and pupicidal activity of Annona senegalensis leaf extract and its 4 fractions against Anopheles gambiae and Culex quinquefasciatus were evaluated in the laboratory conditions. Methods: Ovicidal test was performed by submitting at least 100 eggs of mosquitoes to 125, 250, 500, 1000 and 2000 ppm concentrations, while larvicidal and pupicidal effects were assessed by submitting 25 larvae or pupae to the concentrations of 2500, 1250, 625 and 312.5 ppm of plant extract or fractions of A. senegalensis. Results: The eggs of An. gambiae were most affected by N-hexane (0.00% hatchability) and chloroform (03.67% hatchability) fractions compared to Cx. quinquefasciatus where at least 25 % hatchability were recorded at 2000 ppm. For larvicidal test, N-hexane (LC50= 298.8 ppm) and chloroform (LC50= 418.3 ppm) fractions were more effective than other fractions on An. gambiae larvae while, a moderate effectiveness was also observed with Nhexane (LC50= 2087.6 ppm), chloroform (LC50= 9010.1 ppm) fractions on Cx. quinquefasciatus larvae. The highest mortality percent of the pupae were also recorded with N-hexane and chloroform fractions on An. gambiae at 2500 ppm. As for Cx. quinquefasciatus only 50 % and 36 % mortality were recorded with N-hexane and chloroform fractions respectively. Conclusion: The extract of A. senegalensis was toxic on immature stage of mosquito species tested. By splitting methanolic crude extract, only N-hexane and chloroform fractions were revealed to possess a mosquitocidal effects and could be considered and utilized for future immature mosquito vectors control.